Pengaruh Asam Humat terhadap Produktivitas dan Serapan Nitrogen pada Tanaman Kangkung Darat (Ipomoea reptans Poir.) - Deris Trian Rahmandhias; Diah Rachmawati (Institut Pertanian Bogor, 2020)
An uncertain climate and infertile soils are factors that cause fluctuations in crop yields. In addition, improper application of fertilizers causes kangkong plants to not absorb nutrients optimally. The application of humic acid as a biostimulant can be used to improve soil structure and optimize the productivity of kangkong through the absorption of nutrients from fertilizers or elements around plants. This study aims to study the effect of application of humic acid on growth, productivity, and nitrogen uptake in kangkong (Ipomoea reptans). This research was carried out with completely randomized design (CRD) with a single factor including 7 treatments, namely control, application of humic acid through leaves at a dose of 5 mg.L-1, 20 mg.L-1, and mg.L-1 and through roots a dose of 5 mg.L-1, 20 mg.L-1, and 35 mg.L-1. Planting media used without the addition of basic fertilizers to see the most effective effect of the application of humic acid. The results showed that application of humic acid dose of 20 mg / L through leaves and roots caused an increase in plant height, stem diameter, number of leaves, biomass and nitrogen uptake of kangkong. The highest chlorophyll level of kangkong plants was produced in the treatment of humic acid dose of 35 mg.L-1 through leaves. Based on the research it can be concluded that the application of humic acid through leaves and roots increase growth, productivity and nitrogen uptake in kangkong. Keywords: humic acid, Ipomoea reptans, nitrogen, productivity